Pengaruh Kepemimpinan Transformasional Dan Iklim Organisasi Terhadap Team Work - Tika Mariska; Ranthy Pancasasti (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2022)
technology and information in the field of medicine and health, dr. Drajat Prawiranegara Serang Regency must prepare its nursing staff to be better and more professional in their work. The purpose of this study was to obtain information about the magnitude of the influence of transformational leadership, and organizational climate, on teamwork. This research was conducted at dr. Drajat Prawiranegara (RSDP) Serang Regency. The population in this study is the HR of Nursing Staff at the RSDP with the status of Civil Servants (PNS), totaling 342 people. The number of samples calculated by the Slovin formula, amounted to 77 people. Sampling was done by random sampling method, namely the sample was drawn from the population group at random with the help of Microsoft Excel software. This quantitative research includes survey research, using statistical tests, and PLS Program software version 3.0. The results of this study indicate that transformational leadership has no significant effect on teamwork, organizational climate has a significant effect on teamwork. The research findings show that transformational leadership has no significant effect on teamwork, while organizational climate has a significant effect on teamwork.